A review of mineral exploration drilling with particular reference to Southern Africa - Bertram, N G E (Rhodes University, Faculty of Science, Department of Geology, 1980)
The field of mineral exploration drilling is reviewed with particular reference to examples, and techniques practised, in southern Africa. Drilling is the mostÂ· definitive process in exploration and the most cost intensive. It is, therefore, imperative to insure that the maximum geological information available is obtained from a borehole to warrant the cost of drilling it. Methods and techniques of obtaining this information, at little additional expense, are described and reviewed. Non-core percussion and rotary drilled boreholes cost significantly less than diamond drill holes and, as a result, many more holes can be drilled for the money available. While the logging of cuttings is notoriously neglected in most exploration programmes; a great deal of information is available to the conscientious evaluator. Down-the-hole logging and sampling techniques improve the reliability of the borehole samples and provide rapid and inexpensive analyses and lithological data. Cored, or diamond drill boreholes, are the most versatile of the drilling methods available and provide the most reliable lithological and grade information. The handling, logging, sampling and storage of core and core data is discussed. For little additional expense, comprehensive and accurate borehole surveys can be conducted and oriented cores obtained from the borehole. The natural tendency of a borehole to deviate can be used to advantage with controlled drilling techniques. Multiple ore intersections are possible through controlled deflections from a master hole. Mathematical, statistical and simulation models are available to optimise borehole siting, spacing and grid dimensions .
Keywords: Uncatalogued